Cost-effectiveness of icosapent ethyl, evolocumab, alirocumab, ezetimibe, or fenofibrate in combination with dtatins compared to statin monotherapy - Michaeli, Daniel; Michaeli, Julia; Boch, Tobias; Michaeli, Christoph T. (Clinical drug investigation, 2022)
Despite treatment with statins, dyslipidaemia patients with elevated cholesterol- and triglyceride-levels remain at high residual risk for major adverse cardiovascular events (MACE). New lipid-lowering drugs must prevent the occurrence of MACE and exhibit cost-effectiveness for their successful adoption to clinical practice.